The Effect of Accounting Profit, Operating Cash Flow, Return on Equity (ROE) and Dividends on Stock Trading Volume in Mining Companies Listed on the Indonesia Stock Exchange in 2020-2023 - Dewi, Prita Diana; Sasanti, Elin Erlina (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to test whether accounting profit, operating cash flow, return on equity and dividends affect the volume of stock trading in mining companies listed on the Indonesia Stock Exchange (IDX) for the period of 2020-2023. The sampling technique uses purposive sampling of 21 companies that meet the criteria. The method uses multiple linear regression analysis with the SPSS program. The results of the study show that partially operating cash flow and dividends have an influence on stock trading volume. Meanwhile, accounting profit and return on equity have a significant effect but show a negative influence on stock trading volume. Simultaneously, the results of the study stated that accounting profit, operating cash flow, return on equity and dividends have an effect on stock trading volume.